50th Anniversary Perspective: Conducting/Semiconducting Conjugated Polymers. A Personal Perspective on the Past and the Future - Swager, Timothy M (Macromolecules, 2017)
It has been about 40 years since the field of organic conducting polymers was ignited by the demonstration of metallic conductivity in polyacetylene. A retrospective view of this research area suggests some areas remain ripe for discovery/innovation. The breadth of activities is too large to be comprehensive; hence, selected seminal, as well as some personal, contributions will be used to illustrate concepts and anecdotal ways to think about conducting polymer systems. This Perspective can serve as a tutorial for newcomers to the field and will also remind experts about results from the past. It begins with some history and simple views of electronic structure, with selected examples. Segmented polymers containing isolated redox units will be discussed as well as how these materials can be made to have high conductivity. Key examples illustrating the matching of redox potentials are transition metal hybrid structures. Interchain interactions are emphasized along with their role in determining the nature of the charges. Recent results that demonstrate dramatic magneto-optical properties wherein the transmission of polarized light through conjugated polymers displays dramatic sensitivity to applied magnetic fields (Faraday effect) will also be discussed.